4
$\begingroup$

I tried to prove the inequality

$$2\uparrow^n 4 < 3\uparrow^n 3 < 2\uparrow^n 5$$

for all natural numbers $n\ge 1$

For $n = 1$, the claim is true because of $16 < 27 < 32.$

The left inequality can be proven with induction

$2 \uparrow^{n+1}4 = 2 \uparrow^n(2\uparrow^{n+1} 3) = 2\uparrow^n (2\uparrow^n4) < 2\uparrow^n(3\uparrow^n 3) < 3\uparrow^n(3\uparrow^n 3) = 3\uparrow^{n+1} 3 $

(Please check this proof)

The right inequality is true for $n = 2$ because of

$$3\uparrow \uparrow 3 \approx 7,6 * 10^{12}$$ $$2\uparrow \uparrow 5 \approx 10^{19728}$$

For $n = 3$ we have

$$3\uparrow \uparrow \uparrow 3 \approx 10 \uparrow \uparrow (7,6*10^{12})$$ $$2\uparrow \uparrow \uparrow 5 \approx 10 \uparrow \uparrow (2 \uparrow \uparrow 65536)$$

So, for $n = 3$ the claim is also true.

It seems clear that for bigger $n$, the inequality also holds, but I am looking for a rigorous proof. Perhaps, the base exchange theorem from r.e.s. can help ?

$\endgroup$
6
$\begingroup$

We can generalize the inequalities to:

$$2 \uparrow^m (n+1) < 3 \uparrow^m n < (2 \uparrow^m (n+2))-2$$

for $m,n \ge 2$. We will prove it by double induction.

For $m=2$, we have by an easy induction

$$2 \uparrow\uparrow (n+2) = 2^{2 \uparrow\uparrow (n+1)} < 2^{3 \uparrow\uparrow n} < 3 ^{3 \uparrow\uparrow n} = 3\uparrow\uparrow(n+1)$$

For the right inequality, we instead prove $4 (3 \uparrow\uparrow n) < 2 \uparrow\uparrow (n+2)$.

Base case: $4(3\uparrow\uparrow 2) = 4*27 = 108 < 2\uparrow\uparrow 4 = 65536$.

Induction:

$$2 \uparrow\uparrow (n+3) = 2^{2 \uparrow\uparrow (n+2)} > 2^{4(3\uparrow\uparrow n)} = 16^{3\uparrow\uparrow n} > 4*3^{3\uparrow\uparrow n} = 4(3\uparrow\uparrow (n+1))$$

Next case is $n=2$. For the left inequality we have:

$$2 \uparrow^m 3 = 2\uparrow^{m-1} 4 < 3\uparrow^{m-1} 3 = 3\uparrow^m 2$$

For the right inequality, we use the fact that $2\uparrow^{m-1}4 > 5$. Then

$$2 \uparrow^m 4 - 2 = 2\uparrow^{m-1}(2\uparrow^{m-1}4)- 2 > 2 \uparrow^{m-1}5 - 2 > 3\uparrow^{m-1} 3 = 3\uparrow^m 2$$

Finally, we have the general case $m,n \ge 3$. For the left inequality,

$$2 \uparrow^m (n+1) = 2\uparrow^{m-1} (2 \uparrow ^m n) < 2 \uparrow^{m-1}(3\uparrow^m (n-1)) < 3 \uparrow^{m-1}(3\uparrow^m (n-1)) = 3\uparrow^m n$$

For the right inequality, we have

$$2 \uparrow^m (n+2)-2 = 2\uparrow^{m-1} (2\uparrow^m (n+1)) - 2 > 2\uparrow^{m-1}(3 \uparrow^m (n-1)+2) - 2 > 3\uparrow^{m-1}(3\uparrow^m (n-1)) = 3\uparrow^m n$$

And we're done.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.